Kajian Stilistika dalam "Kidung Ati Tangise Bumi" Karya Yadhy S - Asroh, Hasan; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2024)
The purpose of doing this writing is to examine the style of language which includes diction, imagery, typography, and also figure of speech used in a literary work in the form of Kidung Ati Tangise Bumi by Yadhy S. Due to the purpose of writing which leads to the use of language style, the scalpel The method used to study this literary work is to use a stylistic scalpel. The method used to support this writing is a qualitative descriptive method which is carried out by collecting physical evidence in the form of words, phrases, clauses, and sentences in Kidung Ati Tangise Bumi which are suspected of having links with the scope of use of diction, imagery, typography, and figure of speech. . The results of the research that have been carried out show that this song contains the use of language styles in the form of diction, imagery, figure of speech, and typography which gives its own beauty value in describing a situation.Â